Crack path predictions and experiments in plane structures considering anisotropic properties and material interfaces (Fracture and Structural Integrity, 2015)
In many engineering applications special requirements are directed to a material's fracture behaviorand the prediction of crack paths. Especially if the material exhibits anisotropic elastic properties or fracturetoughnesses, e.g. in textured or composite materials, the simulation of crack paths is challenging. Here, theapplication of path independent interaction integrals (I-integrals), J-, L- and M-integrals is beneficial for anaccurate crack tip loading analysis.Numerical tools for the calculation of loading quantities using these path-invariant integrals are implementedinto the commercial finite element (FE)-code ABAQUS. Global approaches of the integrals are convenientconsidering crack tips approaching other crack faces, internal boundaries or material interfaces. Curved crackfaces require special treatment with respect to integration contours. Numerical crack paths are predicted basedon FE calculations of the boundary value problem in connection with an intelligent adaptive re-meshingalgorithm. Considering fracture toughness anisotropy and accounting for inelastic effects due to small plasticzones in the crack tip region, the numerically predicted crack paths of different types of specimens with material interfaces and internal boundaries are compared to subcritically grown paths obtained from experiments.
Keywords: J-,M-,L-integral